Diffusion brands of designer jeans: effects on brand image and product quality - Phau, Ian (Global Business and Technology Association, 2009)
The study examines how status seeking and fashion innovative young consumers evaluate diffusion brands. Influence of brand naming techniques and country of origin on brand image and product quality of diffusion brands are also examined. The results revealed that sub-brands and nested brands have similar product quality and brand image evaluation when compared to the parent brand. Furthermore, sub-brands and nested brands have demonstrated product quality fit and brand image fit with the parent brand. The findings suggest that a new brand is not a good substitute for the parent brand to express status. In addition, brand origin is a greater signifier of product or brand quality than country of origin.